Non Performing loans Management in Japan during Baburu Keizai, 1989-2001 - Hui, Wong Mei; Abdullah, Alias; Mustapa, Zakaria (WILAYAH: The International Journal of East Asian Studies, 2011)
The abstract is not available. To access, please order the printed version or browse the electronic version of this article.